Organizational and economic mechanism on the sustainable use stimulation of agricultural appointment land - Atamaniuk, O.; Hreshchuk, H. (Land Management, Cadastre and Land Monitoring, 2018)
It is well-known that the use of incentives should lead to an improvement of the existing economic, environmental and social status, to raising the level of economic indicators for the benefit of the person who provides incentives and who is the object of stimulation. The current socio-economic conditions dictate the need to find effective forms of land management and rational land use management, correcting mistakes and resolving existing issues. This is possible only after all agricultural land use is fully provided with the necessary land management works. These issues can be solved by implementing the planning documents for the development of territories (national, regional, local, etc.). They put in place an algorithm of action to address the issue, but the greatest advantage of the proposed development program is the possibility of developing a land management process on agricultural lands. Clear financing of development programs, allows to ensure the implementation of the outlined plans for the implementation of land management works that are necessary on agricultural land. But in the context of the limited economic opportunities of Ukraine, the financing of land management measures provided for by the program should be only partially depending on the possibilities and level of environmental issues of land use.Keywords: agricultural appointment land, sustainable use, stimulation, land management mechanism, development program, land management.